2014
DOI: 10.1074/jbc.m113.543942
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 5′ AMP-activated Kinase as a Target of Reactive Aldehydes during Chronic Ingestion of High Concentrations of Ethanol

Abstract: Background: Carbonylation of proteins contributes to increased hepatocellular damage during alcoholic liver disease. Results: In a murine model of alcoholic liver disease, AMPK is covalently modified by reactive aldehydes reducing activity. Conclusion: Inhibition of AMPK activity by reactive aldehydes contributes to increased steatosis in alcoholic liver disease. Significance: This is the first report of AMPK carbonylation and inhibition during conditions of increased oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 62 publications
5
60
1
Order By: Relevance
“…Consequently, decrease in 4HNE-adduct formation could have contributed to increased activity of AMPKα and a resultant inactivation of ACC. These results are in agreement with the studies demonstrating that 4HNE-mediated carbonylation of AMPKα impairs its kinase function [128]. Taken together, these findings indicate that PDE4 inhibition mediated increase of antioxidant enzymes, AMPKα function and decreased activity of ACC also contributed to decreased lipid accumulation in alcohol fed mice.…”
Section: Pde4 Inhibition Prevents Alcohol Mediated Decrease In Campsupporting
confidence: 82%
See 4 more Smart Citations
“…Consequently, decrease in 4HNE-adduct formation could have contributed to increased activity of AMPKα and a resultant inactivation of ACC. These results are in agreement with the studies demonstrating that 4HNE-mediated carbonylation of AMPKα impairs its kinase function [128]. Taken together, these findings indicate that PDE4 inhibition mediated increase of antioxidant enzymes, AMPKα function and decreased activity of ACC also contributed to decreased lipid accumulation in alcohol fed mice.…”
Section: Pde4 Inhibition Prevents Alcohol Mediated Decrease In Campsupporting
confidence: 82%
“…AMPK mediated phosphorylation of inactivates Acetyl-CoA-carboxylase (ACC), a rate limiting enzyme in fatty acid synthesis, leads to inactivation of ACC and results in decreased lipid accumulation in the liver [62]. There are conflicting reports on alcohol effect on AMPK phosphorylation on Threonine 172 which activates AMPK kinase [62,112,[124][125][126][127][128]. More recently, it has been shown that increased 4NHE levels lead to carbonylation of AMPK which inhibits its kinase activity [128].…”
Section: Pde4 Inhibition Restores Ampk-α Activity and Inactivates Acementioning
confidence: 99%
See 3 more Smart Citations